New names of fossil Rubus (Rosaceae) - Doweld, Alexander B. (Phytotaxa, 2017)
The nomenclature of some fossil homonyms of Rubus is resolved. Fossil Rubus acutiformis M.Chandler, being an illegitimate later homonym of extant R. ×acutiformis Schmidely, is re-named as R. chandlerae nom. nov. R. alnifolius Fotjanova (fossil) is replaced by a new name R. fotjanovae nom. nov., because of the earlier homonym, R. alnifolius Rydberg (extant). Rubus brevis Nikitin (fossil) is replaced by a new name R. laticarpus nom. nov., because of the earlier homonym, R. brevis Gremli (extant). Rubus mammuthicus nom. nov. is proposed to replace the later homonym R. decipiens Nikitin (fossil) non R. decipiens Müller nec R. decipiens Foerster nom. illeg. (extant). Rubus nikitinii nom. nov. is proposed instead of the later homonym R. pygmaeus Nikitin (fossil) non R. pygmaeus Weihe & Nees ex Bluff & Fingerhuth (extant). Rubus aralioides Negru (fossil) is replaced by a new name R. novorossicus nom. nov., because of the earlier homonym, R. aralioides Hance (extant). A new name is proposed for the illegitimate later fossil homonym R. minor Nikitin non Kuntze (extant) (R. tobolicus nom. nov.).